Investigation of Structural Features of Prunes (Prunus domestica) Insoluble Dietary Fibers - Thaisa Moro Cantu-Jungles; Marcello Iacomini; Lucimara MC Cordeiro (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2017)
Structural characteristics of dietary fibers are closely related to its biological functions in the human body. Previously, soluble dietary fibers from prunes were extracted and characterized. In this work, structural analysis of insoluble dietary fibers was conducted using monosaccharide composition, methylation, molecular weight determination and 13C-NMR data. Prunes' non-cellulosic insoluble fibers were found to contain, a pectic type I arabinogalactan, a fucogalactoxyloglucan and a heteroxylan. These findings suggest that insoluble dietary fibers can be composed by some pectic polysaccharides besides cellulose and hemicellulosic polymers. This paper brings important structural features of insoluble dietary fibers from prunes that may be of biological significance.